Actividades y recursos digitales aplicados al proceso enseñanza aprendizaje de Educación Física en Básica Superior, del Colegio Bachillerato Macará, Periodo Lectivo 2023-2024 - Carrión Medina, José Bolívar (2024)
This investigative work is framed in digital activities and resources that can be applied in the teaching-learning process of Physical Education in Upper Basic students of the Macará High School, innovating its methodologies and teaching materials that enrich the training of students and walk at the forefront in the use of ICT. As a general objective; determine the degree of incidence of digital resources applied in the teaching-learning process of Physical Education in upper basic students, of the Macará High School and as short-term objectives; identify the activities and digital resources that are applied in the teaching-learning process of Physical Education, analyze the incidence of digital activities and resources in the teaching-learning process in students, evaluate the activities and digital resources that the institution uses to the teaching-learning process. The study method used was inductive-deductive, it allowed us to discriminate the information from the general to the particular, the research approach is mixed in nature, it helped me test theories and analyze the results, the type of research considered is the correlational, it was used for the collection, measurement and finally the analysis of the data, the research design was longitudinal. After having carried out the analysis of results, it was evident among the most relevant that there is little use and lack of knowledge among students about activities and digital resources that can be used for their teaching process in the subject of Physical Education. The conclusion has been reached, although technology and the use of digital platforms for the training of students in the educational system are currently on the rise, there are educational institutions that do not make use of digital tools, even if the student body is predisposed. in using them.